Twenty Percent. - Armour, Phillip G. (Communications of the ACM, 2007)
This article describes software projects, and how the management of many companies have agreed to probability of completion rates that are as low as 20%. The author reports about many instances where project managers fully expect a late delivery or delayed installation. When the inevitability of a delay becomes obvious, the workload increases to intense levels, causing teams to work in very inefficient and error-inducing ways. The most frequent method that companies use to create estimates is to begin with a plan for the project, which comprises a network of interconnected tasks and predicted dependencies and relationships.